(untitled) (Journal of Informatics Education and Research, 2025)
The rapid emergence of Artificial Intelligence (AI) has reshaped academic processes, influencing how knowledge is created, shared, and evaluated. In the Indian educational landscape, AI-powered tools such as generative text systems, paraphrasing software, automated translation tools, and plagiarism-detection platforms have introduced both significant opportunities and complex ethical challenges. The study following specific objective are: i) to analyse the dual role of AI in relation; and ii) to plagiarism, academic retraction, and integrity within Indian higher education institutions. Despites to AI enhances research efficiency, writing quality, and accessibility, it simultaneously creates new pathways for academic misconduct, including AI-assisted plagiarism, fabricated citations, and unauthorized content generation. Drawing from a review of existing literature, policy documents, and qualitative observations, this research identifies the emerging ethical dilemmas faced by students, researchers, and faculty. The study findings that systemic issues such as limited awareness of AI ethics, inadequate institutional guidelines, digital skill gaps, and increasing pressure for publication and performance in academia. The study findings that academic misconduct in the AI era is rooted not only in technology misuse but also in structural and pedagogical limitations within Indian institutions. The study concludes that the proposing a comprehensive ethical framework, including AI-literacy training, robust institutional policies, enhanced plagiarism-detection systems, and national-level guidelines to strengthen academic transparency and integrity in the digital era.